Biocompatible superhydrophobic coating material for biomedical applications - Mahadik, Satish A.; Pedraza, F.; Mahadik, Sarika S.; Relekar, Brahmanand P.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2017)
Biomaterials and wettability have played a crucial role in the biocompatibility with a host matrix of body fluid and cells. We discuss designing superhydrophobic biomaterials for novel applications such as temporally implant, contact lenses, controlled drug release coatings, coating on medical instruments, etc. Such Superhydrophobic coating surfaces were created with the simple dip coating method by single step base catalyst sol-gel method. Methyltriethoxysilane/trimethoxymethylsilane-based deposition at different dip periods introduces interesting properties in the region, including superhydrophobicity, biocompatibility and transparency. This works reveal the impact of interaction bone marrow mesenchymal stem cells and surface free energy on the biocompatibility of superhydrophobic biomaterial.